Kompetensi Keterampilan Gerak Dasar Siswa Sekolah Dasar di Kota Makassar - Zulfikar, Muhammad (Universitas Cokroaminoto Palopo, 2024)
Fundamental movement skills are the foundation for children to be able to engage in various physical activities after they graduate from school. This research tried to reveal the competency level of fundamental movement skills of elementary school students in Makassar City. The participants in this research were 40 lower class students (male = 24, and female = 16) drawn using stratified random sampling from 4 elementary schools in Makassar City. Data was collected through a basic motor skills test based on the Test of Gross Motor Development 2 (TGMD-2) instrument procedure. The results of the research show that in general the competency level of students' basic movement skills is in the below average category. The research results also showed that there was no difference between the scores of male students and female students.